Land Mapping Study On The Incident Of Diabetes Mellitus In Kalialang Village - Kristiana PH (Sean Institute, 2023)
Prevalence based on international diabetes data (IDF) Indonesia has diabetes mellitus alert status because it ranks 7th out of 10 countries with the highest number of diabetes patients. The prevalence in patients experiencing diabetes mellitus in Indonesia reaches 6.2%. Diabetes Mellitus not only causes premature deaths throughout the world, but can also cause complications in sufferers. Prevention and control need to be carried out to prevent complications. The aim of this research is to determine the Mapping Study on the Incidence of Diabetes Mellitus in Kalialang Village. This research is a non-experimental quantitative research. The research method used was a descriptive analytical design with a cross sectional design, because it did not carry out intervention or treatment and the results of this research were to determine the number of residents suffering from Diabetes Mellitus in Kalialang Village. In this research, we looked at the Mapping Study on the Incidence of Diabetes Mellitus in Kalialang Village. Sampling used the sequential sampling technique, as many as 40 respondents met the inclusion and exclusion criteria. Research tools use observation sheets and questionnaires. Data analysis was carried out univariately, with the aim of identifying each variable in the research. This analysis presents data in the form of mean, median, standard, deviation, maximum value, minimum value for each respondent in terms of age, gender, education level, occupation, length of time suffering from diabetes mellitus. Data is presented in the form of graphs, tables or pie charts and the data is interpreted simply. It is hoped that giving the questionnaire will help determine the incidence of diabetes mellitus in Kalialang Village.